Kebijakan Merdeka Belajar dalam Pelaksanaan Pendidikan di Masa Pandemi Covid-19 - Suhartono, Oki (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2021)
This study aims to examine and analyze the formulation of the independent learning policy formulation in the implementation of education during the Covid-19 pandemic through a SWOT analysis. As we know, the Covid-19 outbreak limits the space for people to move in activities, especially the learning process in schools. So that the existence of an independent learning policy can provide solution steps to overcome the learning process during the Covid-19 pandemic. The research method used is a literature review approach with a descriptive qualitative method. The results show that threats and weaknesses still dominate the existing strengths and opportunities, the availability of human resources, information technology facilities and support from the government authorities are still clashed with the reality of the field in society that is still unable to master technology and budget constraints in managing and supporting the successful implementation of the independent learning policy. during the Covid-19 pandemic. With this article that examines the policy of freedom of learning during the Covid-19 pandemic, it is hoped that there will be further research that directly observes in the field to obtain a more concrete picture to provide alternative solutions in further improvement of government policies.